Flow Visualization in the Water Model of a Molten Aluminum Tundish - F. Shen (The Minerals, Metals and Materials Society, 1993)
Qualitative and quantitative results obtained during the physical modeling of the molten aluminum flow in a tundish using an aqueous system are presented. Surface tuft, free-surface powder and laser sheet visualization techniques were utilized for qualitative studies, whereas laser Doppler velocimetry was used to elucidate the 3-D flow regimes quantitatively. The results of the study are used for validation of the CFD codes, and to explore the effect of the alterations below the nozzle in order to: (1) decrease turbulence levels, and (2) collect the inclusions. Near the nozzle, the interaction of the impinging jet and the inclined walls gives rise to vortex structures. Downstream of the nozzle, two counter-rotating secondary cells diminish in strength. As flow turns through the bend, a separation region is created. The flow heading into the closed duct is seen to be nonsymmetric. A video tape highlighting the major findings is presented.